SOX9 predicts progression towards cirrhosis in patients while its loss protects against liver fibrosis - Athwal, Varinder S.; Pritchett, James; Llewellyn, Jessica; Martin, Katherine; Camacho, Elizabeth; Raza, Sayyid M.A.; Phythian-Adams, Alexander; Birchall, Lindsay J.; Mullan, Aoibheann F.; Su, Kim; Pearmain, Laurence; Dolman, Grace; et al. (Wiley Open Access, 2017)
Fibrosis and organ failure is a common endpoint for many chronic liver diseases. Much is known about the upstream inflammatory mechanisms provoking fibrosis and downstream potential for tissue remodeling. However, less is known about the transcriptional regulation in vivo governing fibrotic matrix deposition by liver myofibroblasts. This gap in understanding has hampered molecular predictions of disease severity and clinical progression and restricted targets for antifibrotic drug development. In this study we show the prevalence of SOX9 in biopsies from patients with chronic liver disease correlated with fibrosis severity and accurately predicted disease progression towards cirrhosis. Inactivation of Sox9 in mice protected against both parenchymal and biliary fibrosis, improved liver function and ameliorated chronic inflammation. SOX9 was downstream of mechanosignaling factor, YAP1. These data demonstrate a role for SOX9 in liver fibrosis and open the way for the transcription factor and its dependent pathways as new diagnostic, prognostic and therapeutic targets in patients with liver fibrosis.